Difficulties Faced Twelfth-grade Students of SMK PGRI 1 Kudus in Speaking English - Chaerunnisa, Audrey Hanindita; Utomo, Slamet; Romadlon, Farid Noor (Universitas Muria Kudus, 2025)
Speaking is the process of expressing ideas, thoughts, emotions, or information through oral communication, serving as a key tool for exchanging messages between individuals. Speaking can be particularly difficult for English language learners to master because it needs not only the ability to pronounce words correctly, knowledge of vocabulary and grammar (linguistic), but also anxiety, a lack of practice opportunities, and insufficient exposure to actual spoken English can all limit the learning process (non-linguistic). This study aims to investigate the difficulties students have when learning English, particularly focusing on improving their speaking skills, and the techniques they use to overcome those difficulties.The study uses a case study research design and a qualitative approach and focuses on twelfth-grade Beauty and Spa major students at SMK PGRI 1 Kudus during the 2024/2025 academic year. The sample group consists of 27 students from the XII KS 1 class, with data collected through questionnaires and interviews.The findings indicate that students' motivation to learn English speaking improves when they receive positive support from peers, teachers, and family. Common struggles include fluency issues, difficulties in expressing thoughts, using correct tenses, and communicating clearly in English. To address these difficulties, students employ various strategies, such as using language-learning apps, participating in English clubs, watching English media with subtitles, and practicing independent speaking through self-narration and recordings. To further enhance their speaking skills, students can engage in activities like taking courses, joining extracurricular activities, using both school-provided and online English learning apps, and actively practicing speaking.